Jessica Jones. The complete first season [videorecording (DVD)] - Clarkson, S. J.; Petrarca, David; Ritter, Krysten, 1981-; Taylor, Rachael; Darville, Eka, 1989- (Walt Disney Studios Home Entertainment, 2017)
After the end of her superhero career, Jessica Jones sets herself up as a private investigator in Hell's Kitchen.